"It can't happen here": Trump, authoritarianism and American politics. (February 2017) - Burston, Daniel
Abstract: Donald Trump's election on November 8, 2016, alarmed many people in the United States and around the world. Explanations for his popularity vary widely, but prominent among them is the idea of authoritarianism, or the authoritarian personality. Current discussions of authoritarianism in sociology and political science generally adopt (or adapt) the version as outlined by Adorno, Frenkel‐Brunswik, Levinson, andSanford, which first appeared in 1950 in the United States but generally ignore the earlier articulations of "the authoritarian character", which were psychoanalytic, and stressed the sado‐masochistic character traits that presumably prompted people to support fascistic leaders, and which appeared in the 1930s in Germany. This paper reviews the history of the concept of authoritarianism, and the ways in which recent discussions of sado‐masochism in the clinical arena have, with rare exceptions, become detached from discussions of authoritarianism in the sociological and political science literature. It ponders the applicability of this concept to the Trump Presidency, and the parallels between the situation in Weimar in the 1930s and the United States today.